Production of rhodomycins in Streptomyces griseoruber 4620 - Podojil, M; Blumauerová, M; Prikrylová, V; Vanĕk, Z; Gauze, G F; Maksimova, T S (Folia microbiologica, 1980)
The strain Streptomyces griseoruber 4620 produces, besides the anthracycline antibiotics beromycins, some other anthracyclines of the rhodomycin type. Twelve isolates exhibiting a higher antibiotic activity (up to 2.5X), as compared to the parent strain, were obtained after a spontaneous selection. The following species were isolated from the hydrolysate of mycelial extract: beta-rhodomycinone, beta-isorhodomycinone, alpha 2-rhodomycinone, epsilon-rhodomycinone and 10-deoxy-beta-rhodomycinone, which has not yet been described.
Keywords: antibakteriální látky; Streptomyces; naftaceny; antracykliny; Naphthacenes; Anthracyclines; Anti-Bacterial Agents